IDENTITY POSITIONS AND HALAL COSMETICS IN INDONESIAN MIDDLE-CLASS MUSLIM WOMEN - Abhirama SD Perdana (Expose: Jurnal Ilmu Komunikasi, 2018)
Creations can become meaningful when there are audience who pay attention towards theproducts, enjoy and show their appreciation or even evaluation towards them. The meaning produced within amedia is considered incomplete without the understanding of the audience and the meaning the audienceproduces in appreciating as well as responding to the media text. To understand more on the meaning of textmedia, therefore, it is paramount to consider and gain a thorough understanding of the meaning produced by themedia audience through studying the way the audience reads, uses, and responds to the media. Utilizing Hall’sCultural Studies of dominant and oppositional readings, this paper endeavours to showcase the understanding ofaudience and how meaning is constructed. Locating the issue of audience research in the context of HalalCosmetics and the Middle-Class Muslims in Indonesia, a brief overview on the theories of audience is outlinedand relevant theories to the case of integrating advertisement in Indonesian cinema is employed.